Centromere RNA is a key component for the assembly of nucleoproteins at the nucleolus and centromere - Wong, Lee H.; Brettingham-Moore, Kate H.; Chan, Lyn; Quach, Julie M.; Anderson, Melisssa A.; Northrop, Emma L.; Hannan, Ross; Saffery, Richard; Shaw, Margaret L.; Williams, Evan; Choo, K.H. Andy

(untitled) (Genome Research, 2007)
The centromere is a complex structure, the components and assembly pathway of which remain inadequately defined. Here, we demonstrate that centromeric α-satellite RNA and proteins CENPC1 and INCENP accumulate in the human interphase nucleolus in an RNA polymerase I–dependent manner. The nucleolar targeting of CENPC1 and INCENP requires α-satellite RNA, as evident from the delocalization of both proteins from the nucleolus in RNase-treated cells, and the nucleolar relocalization of these proteins following α-satellite RNA replenishment in these cells. Using protein truncation and in vitro mutagenesis, we have identified the nucleolar localization sequences on CENPC1 and INCENP. We present evidence that CENPC1 is an RNA-associating protein that binds α-satellite RNA by an in vitro binding assay. Using chromatin immunoprecipitation, RNase treatment, and “RNA replenishment” experiments, we show that α-satellite RNA is a key component in the assembly of CENPC1, INCENP, and survivin (an INCENP-interacting protein) at the metaphase centromere. Our data suggest that centromere satellite RNA directly facilitates the accumulation and assembly of centromere-specific nucleoprotein components at the nucleolus and mitotic centromere, and that the sequestration of these components in the interphase nucleolus provides a regulatory mechanism for their timely release into the nucleoplasm for kinetochore assembly at the onset of mitosis.